Sn and Cu influence on Mg:Si ratios evolution in clusters based on DFT and its impact on precipitation hardening of pre-aged Al-1.0Mg-0.6Si alloys - Fengkai Lu; Jianguo Tang; Wenbin Tu; Huijin Tao; Lingying Ye; Shengdan Liu; Xin Zhan; Lehang Ma; Xiyan Hu; Chenlu Yu (Journal of Materials Research and Technology)
Using atom probe tomography (APT), transmission electron microscopy (TEM), and hardness tests, the effect of Sn and Cu on the evolution of Mg:Si ratios in clusters and subsequent precipitation hardening behavior of pre-aged Al-1.0Mg-0.6Si alloys are investigated, and the underlying mechanism is revealed by density functional theory (DFT) calculation of interaction energy. It is shown that, the doping of Sn and/or Cu increases the average Mg:Si ratio in clusters. This increase is attributed to the strong interaction of Sn/Cu with Mg solutes, which enhances the binding of Mg to Si-rich clusters and results in a higher proportion of clusters with Mg:Si ratios near 1 (0.75–1.25). Consequently, the enhanced precipitation of β'' precipitates during artificial aging is observed in Sn and/or Cu doped alloys, due to the ease of clusters with Mg:Si ratios near 1 transform into β'' precipitates, leading to an improved hardening response. Notably, the combined doping of Sn and Cu exhibits the strongest aggregation tendency towards Mg solutes, yielding the most pronounced strengthening effects on precipitation and hardening response during artificial aging. Furthermore, a schematic model detailing the evolution of Mg:Si ratios in clusters is proposed, based on the APT results and DFT calculation of interaction energy.